Knockdown of Circular RNA hsa_circ_PVT1 Inhibited Laryngeal Cancer Progression via Preventing wnt4/β-Catenin Signaling Pathway Activation - Yu, Feng; Lin, Ying; Ai, Mao-Mao; Tan, Guo-Jie; Huang, Jia-Li; Zou, Zi-Rou (Frontiers in Cell and Developmental Biology, 2021)
Aim: To explore the function and mechanism of circular has_circ_PVT1 on laryngeal cancer. Method: Microarray chip was performed to screen the differentially expression circRNA. Western blot and qRT-PCR was employed to detect the protein and mRNA level. CCK-8, clone formation, cell cycle, wound healing, Transwell assay were performed to detect the cell proliferation, migration and invasion ability. Luciferase assay and Fish were used to confirm the relationship between circ_PVT1/CBX4 and miR-21-5p. Flow cytometry and TUNEL assay were carried out to assess the apoptosis level. Results: The up-regulated of circ_PVT1 was found in laryngeal cancer tissues and cells. Silencing of circ_PVT1 inhibited laryngeal cancer progression via targeting miR-21-5p and indirectly controlling CBX4. Wnt4/β-catenin signal pathway was inactivated by inhibiting the expression of circ_PVT1. Conclusion: Knockdown of circ_PVT1 prevented laryngeal cancer progression via targeting miR-21-5p/CBX4 by inhibiting wnt4/β-catenin signal pathway, which could be provided a novel therapy target of laryngeal cancer.